Optical Constants of Chemical Vapor Deposited Graphene for Photonic Applications - Marwa A. El-Sayed; Georgy A. Ermolaev; Kirill V. Voronin; Roman I. Romanov; Gleb I. Tselikov; Dmitry I. Yakubovsky; Natalia V. Doroshina; Anton B. Nemtsov; Valentin R. Solovey; Artem A. Voronov; Sergey M. Novikov; Andrey A. Vyshnevyy; et al. (Nanomaterials, 2021)
Graphene is a promising building block material for developing novel photonic and optoelectronic devices. Here, we report a comprehensive experimental study of chemical-vapor deposited (CVD) monolayer graphene’s optical properties on three different substrates for ultraviolet, visible, and near-infrared spectral ranges (from 240 to 1000 nm). Importantly, our ellipsometric measurements are free from the assumptions of additional nanometer-thick layers of water or other media. This issue is critical for practical applications since otherwise, these additional layers must be included in the design models of various graphene photonic, plasmonic, and optoelectronic devices. We observe a slight difference (not exceeding 5%) in the optical constants of graphene on different substrates. Further, the optical constants reported here are very close to those of graphite, which hints on their applicability to multilayer graphene structures. This work provides reliable data on monolayer graphene’s optical properties, which should be useful for modeling and designing photonic devices with graphene.